Dental health status and Oral Health-Related Quality of Life in older people of Puerto Montt, Chile. - Evelyn Piticar; Lorena-Mirtala Orellana (Universidad de Concepción., 2020)
Introduction: Older people tend to have poor oral health, which can affect their quality of life. This study aimed to explore the relationship of the Oral Health-Related Quality of Life (OHRQoL) with sociodemographic variables and the dental health status of older people who belong to Elderly Clubs in the district of Puerto Montt, Chile. Material and methods: A cross-sectional study was carried out in 140 elderly people from Elderly Clubs in the district of Puerto Montt, Chile. Sociodemographic and dental variables were studied using a questionnaire and clinical examination. The GOHAI instrument validated in Chile was applied to measure the OHRQoL. Results: The mean of the total GOHAI was 50.8±8.6 points, and the median was 53. Of the 140 elderly people, 87.9% were females, the means of age and years of education were 73.2±6.2 and 7.5±4.4 years, respectively. 30% were edentulous, the number of remaining teeth was 7.8±8.1, the OHI-S was 1.3±1.0. 85.7% wore dentures, and the time of denture wearing was 8.8±9.4 years. Significant associations were found between the total GOHAI and non-belonging to an indigenous people (p=0.024), being edentulous (p=0.006), and the presence of healthy teeth (p=0.039). Conclusion: The GOHAI showed a significant relationship with not-belonging to an indigenous ethnicity, being edentulous, and the number of healthy teeth. The OHRQoL was higher in males, with formal education, edentulous, dentated without teeth mobility, with complete dentures, and moderate denture hygiene.